Rancangan dan Efektifitas Media Pembelajaran Audiovisual pada Mata Kuliah Bahasa Prancis Pariwisata - Putu Weddha Savitri; A.A. Sg. Shanti Sari Dewi (Udayana University Press bekerjasama dengan Fakultas Ilmu Budaya Universitas Udayana, 2024)
The Covid-19 pandemic has brought considerable changes in the world of education. Learning methods that were previously carried out face-to-face must switch to online methods. This requires teacher innovation and creativity so that learning material can be conveyed properly. One of the learning media that is very helpful in distance learning is to use audiovisual media. This research is a needs analysis that aims to be able to find out the responses and needs of students towards the audiovisual media used so far in French Language Courses. Qualitative and quantitative methods were used in analyzing data in the form of questionnaires and interviews. The results of the analysis show that the use of audiovisual media as learning material gets a positive response from students. Students also hope that audiovisual material can be developed even better, including short durations, added interesting animations, subtitles so that students understand conversations, as well as repetition in terms of pronunciation and material summaries at the end of the video.